1988
DOI: 10.1111/j.1460-2695.1988.tb01219.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Fatigue Crack Growth Characterisation by Linear Elastic Fracture Mechanics (Lefm). Part I—principles and Methods of Data Generation

Abstract: Ahstmet-The application of linear elastic fracture mechanics (LEFM) to the characterisation of fatigue crack growth has been reviewed. In Part I the present understanding of the factors influencing growth rate is summarised, and the current methods of fatigue crack growth rate data generation are considered in the light of this. In Part 11, documents are reviewed which provide advice on the prediction of fatigue crack growth and also those national standards in which fatigue crack growth considerations are imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 53 publications
0
16
0
2
Order By: Relevance
“…The technique for the determination of crack closure was later used by most researchers with little modifications for the crack opening displacement measurement and interpretation of crack closure or opening levels. A great number of technical papers related to crack closure have been published in the last three decades (Allen et al, 1988;McClung, 1999;Sehitoglu et al, 1996;Vasudeven et al, 1994). Noticeably, two volumes of ASTM Special Technical Publications, ASTM STP 982, and ASTM STP 1343, were specifically dedicated to the discussion of crack closure.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The technique for the determination of crack closure was later used by most researchers with little modifications for the crack opening displacement measurement and interpretation of crack closure or opening levels. A great number of technical papers related to crack closure have been published in the last three decades (Allen et al, 1988;McClung, 1999;Sehitoglu et al, 1996;Vasudeven et al, 1994). Noticeably, two volumes of ASTM Special Technical Publications, ASTM STP 982, and ASTM STP 1343, were specifically dedicated to the discussion of crack closure.…”
Section: Introductionmentioning
confidence: 98%
“…Noticing the overestimated crack closure effect, partial crack closure concept was developed by introducing a coefficient being less than unit as a multiplier to S op (Paris et al, 1999;Kujawski, 2002Kujawski, , 2003. On the other hand, Allen et al (1988) concluded that at a growth rate of the order of 10 À5 mm/ cycle and greater, closure did not occur except in the presence of shear lips. Vasudeven et al (1994) critically reviewed the published crack closure mechanisms for the near-threshold crack growth behavior and concluded that there can be no contribution from plasticity to crack closure.…”
Section: Introductionmentioning
confidence: 99%
“…The overall energy release rate can then be obtained from Eqs (14) and (6) as a combination, through constant coefficients, of the derivatives of functions zi(a) (i = 1,2 and eventually 3) once the slope of the stress diffusion lines, i.e. the function p(a), has been determined.…”
Section: Ismentioning
confidence: 99%
“…A simple and reliable tool that can be used for this kind of analysis is the Linear Elastic Fracture Mechanics . Many laws for fatigue crack propagation are available (e.g.…”
Section: Introductionmentioning
confidence: 99%